Concretos produzidos com adição de resíduo proveniente do sistema de dessulfurização de gases (FGD): avaliação de aspectos mecânicos, ambientais e de durabilidade - Teixeira, Roberta Arleu (2019)
The use of industrial waste in civil construction has been presented as an excellent alternative, from the economic, environmental and social points of view, since it allows the reinsertion of waste in the production cycle, avoiding the generation of waste, and also contribute to a reduction in the consumption of natural resources by the construction industry. The FGD process is an alternative for the control of SOx emissions in thermoelectric and steel plants, but it generates a residue, with similar characteristics to the additions used to improve the properties of the building materials. Since concrete is the most widely used material in the world, alternatives that promote greater sustainability in its production are essential. In this way, this research aimed to evaluate the performance of concrete produced with addition of the FGD residue in 0%, 5%, 10% and 15% of the cement mass, using two water / binder ratios of 0.45 and 0.6. The concretes were evaluated at the ages of 7, 28, 56 and 91 days. In the fresh state, the consistency index and the specific mass were determined. In the hardened state the evaluated properties had the objective to determine parameters of mechanical performance and durability of concretes. Compressive Strength, Tensile Strength by Diametral Compression, Water Absorption by Immersion and by Capillarity, Total and Soluble Chloride Content and Soluble Sulphate Content were evaluated. The microstructure of the concretes and the leaching of contaminants according to NEN 7375 (NNI, 2004) were also evaluated. ANOVA of the results obtained was performed. As results, it was obtained that the use of the FGD waste as addition in concretes is technically feasible, being the best performance obtained for the content of 5% of addition, that besides promoting a greater increase in the resistance to compression, guaranteed the resistance to the traction of the concrete reference and contributed to a better compactness of the concrete, reducing the absorption of water by immersion and capillarity of the concrete studied. Finally, it has been found that the use of the FGD residue is environmentally safe.